HIGH-TEMPERATURE HEAT CAPACITY AND THERMODYNAMIC PROPERTIES FOR END-MEMBER TITANITE (CATISIO5) - Tangeman J.; Xirouchakis D. (My University, 2001)
The heat capacity of end-member titanite and (CaTiSiO5) glass has been measured in the range 328–938 K using differential scanning calorimetry. The data show a weak λ-shaped anomaly at 483 ± 5 K, presumably associated with the well-known low-pressure P21/a ⇆ A2/a transition, in good agreement with previous studies. A value of 0.196 ± 0.007 kJ mol−1 for the enthalpy of the P21/a ⇆ A2/a transition was determined by integration of the area under the curve for a temperature interval of 438–528 K, bracketing the anomaly. The heat capacity data for end-member titanite and (CaTiSiO5) glass can be reproduced within <1% using the derived empirical equations (temperature in K, pressure in bars):$$$$ $$$$ The available enthalpy of vitrification (80.78 ± 3.59 kJ mol−1), and the new heat capacity equations for solid and glass can be used to estimate (1) the enthalpy of fusion of end-member titanite (122.24 ± 0.2 kJ mol−1), (2) the entropy of fusion of end-member titanite (73.85 ± 0.1 J/mol K−1), and (3) a theoretical glass transition temperature of 1130 ± 55 K. The latter is in considerable disagreement with the experimentally determined glass transition temperature of 1013 ± 3 K. This discrepancy vanishes when either the adopted enthalpy of vitrification or the liquid heat content, or both, are adjusted. Calculations using Eq. (2), new P−V−T data for titanite, different but also internally consistent thermodynamic data for anorthite, rutile, and kyanite, and experimental data for the reaction: anorthite + rutile = titanite + kyanite strongly suggest: (1) the practice to adjust the enthalpy of formation of titanite to fit phase equilibrium data may be erroneous, and (2) it is probably the currently accepted entropy of 129.2 ± 0.8 J/mol K−1 that may need revision to a smaller value.
Keywords: Titanite; Heat capacity; Entalpy; Entropy; Lambda transition